2022
DOI: 10.1097/sap.0000000000003116
|View full text |Cite
|
Sign up to set email alerts
|

Prelamination of the Radial Forearm Free Flap Using Free Full-Thickness Eyelid Skin Grafts

Abstract: Free flap transfer for reconstruction of intraoral defects is a common procedure in oral and maxillofacial surgery. For tumor-related defects, the radial forearm flap is widely used for soft tissue restoration. However, transfer of free skin grafts to the donor site region is often required for wound closure after free flap harvesting, resulting in esthetic disturbances due to shrinkage of the grafted skin, attendant scarring, or mismatches in skin texture or color. Furthermore, free flap transfer may result i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The reconstructive approach is determined by the defect's extent, with local flaps serving well in limited defects [4][5][6] ; however, extensive, full-thickness deficiencies often necessitate more intricate procedures, such as free tissue transfer. [7][8][9][10][11][12][13] The radial forearm free flap (RFFF) is a well-established method for reconstructing considerable defects in the head and neck region, particularly when thin and pliable tissue is required. The flap's pedicle length is pivotal, with the radial forearm offering the necessary length for microvascular anastomosis.…”
Section: Introductionmentioning
confidence: 99%
“…The reconstructive approach is determined by the defect's extent, with local flaps serving well in limited defects [4][5][6] ; however, extensive, full-thickness deficiencies often necessitate more intricate procedures, such as free tissue transfer. [7][8][9][10][11][12][13] The radial forearm free flap (RFFF) is a well-established method for reconstructing considerable defects in the head and neck region, particularly when thin and pliable tissue is required. The flap's pedicle length is pivotal, with the radial forearm offering the necessary length for microvascular anastomosis.…”
Section: Introductionmentioning
confidence: 99%
“…Free flaps exhibit good compatibility with head and neck defects, ensuring good functional and aesthetic outcomes. [5][6][7] Several studies have reported that free flap transplantation in patients with head and neck tumors can improve skin defects, thereby enhancing skin functionality and appearance, and having considerable therapeutic value. [5,[8][9][10] However, free flap surgeries are associated with multiple perioperative complications; therefore diligent perioperative care is crucial for the success of the procedure.…”
Section: Introductionmentioning
confidence: 99%